Perbandingan Kualitas Patient Engagement Pada Empat Pelayanan Spesialis Dasar Di RSUD Haji Provinsi Sulawesi Selatan - Andi Tihardimanto K (Al-Hikmah Journal for Religious Studies, 2014)
AbstractThis research aimed to describe and compare the patient engagement quality of the four basic specialist services in the in-patient installation in Haji Local General Hospital of South Sulawesi Province. This research was a comparative descriptive research. The research sample comprised the group respondents of in-patients the four basic specialist services. The result of the research revealed that patient engagement quality as perceived by the patients was categorized as good (73,9%); the patient engagement related to the doctor's capacity to listen to  and  encourage  the  patients  to  ask  questions  was  categorized  as  good (78,4%); in making a decisions was not good (63,6%); the ability of the doctor to  give  and  explain  the  information  to  patients  was  good  (63,1%).  The duration of consultation was good (56,8%); while the empathy given to the patients was categorized as good (83,5%). As for the quality of the patient engagement in the four sub-parts of the basic specialist services, the quality of the patient engagement was significantly different from one another (p=0,000).